Quinidine-responsive out-of-hospital polymorphic ventricular tachycardia in patients with coronary heart disease. Issue 2 (12th November 2019) - Viskin, Sami; Hochstadt, Aviram; Chorin, Ehud; Viskin, Dana; Havakuk, Ofer; Khoury, Shafik; Lee, John K; Belhassen, Bernard; Rosso, Raphael
Abstract: Aims: We recently reported that patients with coronary artery disease (CAD) who develop polymorphic ventricular tachycardia (VT) during the healing phase of an acute coronary event, generally fail to respond to revascularization or standard antiarrhythmic therapy but respond immediately to quinidine therapy. Here, we describe that CAD patients presenting with out-of-hospital polymorphic VT without a recent coronary event or an obvious precipitating factor, also respond uniquely to quinidine therapy. Methods and results: Retrospective study of patients with unheralded, mainly out-of-hospital, polymorphic VT related to CAD but without evidence of acute myocardial ischaemia. We identified 20 patients who developed polymorphic VT without precipitating factors. The polymorphic VT events were triggered by extrasystoles with short (376 ± 49 ms) coupling interval. Arrhythmic storms occurred in 70% patients. These arrhythmic storms were generally refractory to conventional antiarrhythmic therapy but invariably responded to quinidine therapy. Revascularization was antiarrhythmic in 3 patients despite the absent clinical or ECG signs of ischaemia. During long-term follow-up (range 2 months to 11 years), 3 (15%) of patients not receiving quinidine developed recurrent polymorphic VT. There were no recurrent arrhythmias during long-term quinidine therapy. Conclusions: Patients with CAD may develop polymorphic VT in the absence of obvious acute ischaemia or apparent precipitating factors, presenting as out-of-hospital polymorphic VT with high risk of arrhythmic storms that respond uniquely to quinidine therapy.